From learning objects repositories to learning design repositories: The COSMOS learning design repository - Sampson, Demetrios; Zervas, P.; Sotiriou, S. (2011)
During the past years sharing and re-use of digital science education resources became a mainstream activity among science education communities. These resources bare the potential to support technology-enhanced science education by enabling science education teachers to improve their day-today science teaching. On the other hand, it has been identified that science education teachers could benefit from their participation in communities of best science teaching practices by sharing, not only digital educational resources, but learning designs that reflect their pedagogical practice. This has lead to efforts on moving beyond web-based repositories of digital educational content towards the development of web-based repositories of learning designs. Nevertheless, sharing learning designs requires tools and strategies, so as to facilitate the representation of these learning designs in a commonly understandable manner between humans and machines. To this end, we present the design and operation of the COSMOS web-based repository of Learning Designs for supporting Science Education Teacher Communities. © 2011 IEEE.